2016
DOI: 10.1097/brs.0000000000001476
|View full text |Cite
|
Sign up to set email alerts
|

ISSLS Prize Winner: Consensus on the Clinical Diagnosis of Lumbar Spinal Stenosis

Abstract: Study Design Delphi. Objective Obtain an expert consensus on which history factors are most important in the clinical diagnosis of LSS. Summary of Background Data Lumbar spinal stenosis (LSS) is a poorly defined clinical syndrome. Criteria for defining LSS are needed and should be informed by the experience of expert clinicians. Methods Phase 1 (Delphi Items): 20 members of the International Taskforce on the Diagnosis and Management of LSS confirmed a list of 14 history items. An on-line survey was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 47 publications
0
55
0
2
Order By: Relevance
“…The overall prevalence of lumbar spinal stenosis varies among studies. The prevalence in the group based on clinical diagnostic criteria has been reported to be approximately 11% in the general population [ 13 - 15 ]. According to the diagnosis based on imaging studies, the prevalence was found to be 11% in the asymptomatic general population and 38% in the general population.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…The overall prevalence of lumbar spinal stenosis varies among studies. The prevalence in the group based on clinical diagnostic criteria has been reported to be approximately 11% in the general population [ 13 - 15 ]. According to the diagnosis based on imaging studies, the prevalence was found to be 11% in the asymptomatic general population and 38% in the general population.…”
Section: Prevalencementioning
confidence: 99%
“…Till date, there exists some ambiguity in the clinical diagnostic criteria for degenerative lumbar spinal stenosis. According to a study conducted in 2016, the consensus of experts on clinical symptoms included (1) pain in the lower extremities or buttocks while walking, (2) symptom relief resulting from bending the lower back forward, (3) symptom relief from bending the back forward while using a shopping cart or riding a bicycle, (4) motor or sensory disturbance while walking, (5) normal and symmetrical pulse of the dorsalis pedis artery, (6) weakening of lower extremity, and (7) lower back pain [ 13 , 14 ]. In other studies, detailed history, gait, and some physical examination findings were also included in the classification criteria [ 13 , 15 , 19 ].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…As with disc herniations, stenosis is common in asymptomatic persons (4%–28%) [100] , [101] . The diagnosis of the clinical syndrome of lumbar spinal stenosis requires both the presence of characteristic symptoms and signs as well as imaging confirmation of narrowing of the lumbar spinal canal or foramina [102] .…”
Section: Common Spine Degenerative Imaging Findings In Patients With mentioning
confidence: 99%
“…Thus, attempts to reduce the recurrent herniation have been tried again and again, and annular repair may be an answer. First reported by Yasargil in 1977 [22] and subsequently by others [23,24], the annular repair is considered as a valuable method to close the defect and subsequently prevent recurrent herniation.…”
Section: Discussionmentioning
confidence: 99%